2008
DOI: 10.1007/s10827-008-0114-6
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation-driven rhythmogenesis in an excitatory neuronal network with slow adaptation

Abstract: The publisher regrets that a reference was incorrectly printed for the article, "Fluctuation-driven rhythmogenesis in an excitatory neuronal network with slow adaptation," by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…For instance, coherent oscillations in one-population spiking neural networks where exhibited by Pham and collaborators [45]. The results obtained by Nesse and collaborators [42] also confirm the presence of noise-induced phenomena in all-to-all coupled networks of leaky integrate-and-fire neurons with filtered noise and slow activity-dependent currents, i.e. noise and spikes are filtered by a second order kernel.…”
Section: Meanmentioning
confidence: 64%
“…For instance, coherent oscillations in one-population spiking neural networks where exhibited by Pham and collaborators [45]. The results obtained by Nesse and collaborators [42] also confirm the presence of noise-induced phenomena in all-to-all coupled networks of leaky integrate-and-fire neurons with filtered noise and slow activity-dependent currents, i.e. noise and spikes are filtered by a second order kernel.…”
Section: Meanmentioning
confidence: 64%
“…The mean rate and variance were gradually increased from F n = 0 to F n = 1 kHz, as suggested by Rodriguez-Molina et al (2007). Similar approaches were also suggested in other studies, e.g., Nesse et al (2008). In the pacemaker-driven simulations we kept all input parameters within the same physiological ranges as before, except that the noise was set at zero and pacemaker features were assigned to the intense neurons.…”
Section: Simulation Modelmentioning
confidence: 87%
“…We kept all model parameters, except the network size, in a constant range in order to have a common point of reference. For small networks created with this setup, parameter ranges were similar to those reported in literature, e.g., Wiedemann and Luthi (2003), Giugliano et al (2004), and Nesse et al (2008). By changing the network size from n = 500 to 5,000 and keeping K max constant, the average number of connections (or "average connection probability") between two randomly chosen neurons was reduced from 1 to 0.1.…”
Section: Network Simulation With Homogeneous Synaptic Strength Distrimentioning
confidence: 99%
See 1 more Smart Citation
“…The less used 'pacemaker-driven' approach is based on intrinsically active cells, as described by Latham et al (2000a,b). Recent modeling studies showed that theoretically both the approaches can provide robustness of network bursting behavior in noisedriven (Nesse et al 2008) and pacemaker-driven networks (Vladimirski et al 2008). However, Vladimirski et al (2008) showed that homogeneous noise-driven networks produced fragile rhythmic bursts.…”
Section: Introductionmentioning
confidence: 99%